The Role Of The Tourism Sector In Increasing Economic Development On The Per Capita Income Of The Timor Leste Community - Agapito Barros; Sudarto, Sudarto (International Journal of Technology and Education Research, 2024)
Timor Leste, a small country located in Southeast Asia, has great potential in the tourism sector that has not yet been fully explored. With stunning natural beauty, such as pristine beaches, green mountains, and rich cultural diversity, Timor Leste has a strong attraction for domestic and foreign tourists. This research aims to explore how the tourism sector can play a role in increasing economic development in Timor Leste, especially in relation to people's per capita income. The sample in this study amounted to 197 respondents and was analyzed using SemPLS. The results of this research are that this research can be concluded that Accessibility and Transportation have an effect on Community Per Capita Income. Featured Tourist Destinations have no effect on Community Per Capita Income. Increasing Tourism Environmental Awareness has an effect on Community Per Capita Income. Local Community Empowerment influences Transportation. Local Community Empowerment influences Community Per Capita Income. MSME Development has no effect on Accessibility and Transportation. Increasing Tourism Environmental Awareness does not moderate Accessibility and Transportation on Community Per Capita Income. Promotion of Cultural and Heritage Tourism has no effect on Accessibility and Transportation. Tourist infrastructure has no effect on Accessibility and Transportation